Governing Before the Bid: The Prequalification-Enforced Reverse Auction Framework for ERP-Embedded Public Sector Procurement - Vijaya Bhaskar Reddy Saadhu (International Journal of Engineering, Science and Information Technology, 2026)
Competitive price discovery through electronic reverse auctions depends on enforcing vendor eligibility before the auction process begins rather than after contract award. In many public-sector Enterprise Resource Planning (ERP) systems, however, vendor prequalification is still managed through manual administrative procedures instead of embedded system controls, creating compliance gaps that lead to post-award disqualifications, procurement delays, audit findings, and inconsistent procurement outcomes. This article introduces the Prequalification-Enforced Reverse Auction (PERA) framework, a three-layer architectural model that embeds vendor prequalification directly into ERP reverse auction modules through user interface (UI)-level constraint mechanisms. The framework consists of Event-Level Lock, Participant-Level Lock, and Qualification-Level Lock, which collectively ensure that only vendors satisfying predefined eligibility requirements are permitted to participate in auction events. Vendor qualification is evaluated using a ten-dimensional Boolean assessment model organized into three governance domains: Technical and Operational Readiness, Financial and Commercial Governance, and Risk and Regulatory Control. To further improve procurement quality, the framework incorporates a price-signal diagnostic mechanism that analyzes preliminary pricing variance to identify potential specification ambiguity before auction creation. The proposed architecture was evaluated using implementation evidence from approximately 120 government agencies and more than 200 reverse auction events conducted within a state-level ERP procurement platform. The findings indicate that PERA substantially reduces post-award vendor disqualification incidents, improves regulatory compliance, standardizes vendor eligibility enforcement across agencies, and shortens procurement cycle times to approximately 60 minutes per auction event. By transforming prequalification from an administrative responsibility into an automated architectural constraint, the framework enhances transparency, fairness, auditability, and operational efficiency. The proposed PERA architecture provides a scalable and transferable design model for ERP-based public procurement systems without requiring changes to existing procurement regulations or upstream governance frameworks